Mutational analysis reveals separable DNA binding and trans-activation of Drosophila STAT92E. - Karsten, P.; Plischke, I.; Perrimon, N.; Zeidler, M.P. (Cellular Signalling, 2006)
In the canonical model of JAK/STAT signalling STAT transcription factors are activated by JAK mediated tyrosine phosphorylation following pathway stimulation by external cytokines. Activated STAT molecules then homo- or heterodimerise before translocating to the nucleus where they bind to DNA sequences within the promoters of pathway target genes. DNA-bound STAT dimers then activate transcription of their targets via interaction with components of the basal transcription machinery. Here we describe a missense mutation in the SH2 domain of the single Drosophila STAT92E homologue which results in an amino-acid substitution conserved in both the canonical SH2 domain and STAT-like molecules previously identified in C. elegans and the mosquito Anopheles gambiae. This mutation leads to nuclear accumulation and constitutive DNA binding of Drosophila STAT92E even in the absence of JAK stimulation. Strikingly, this mutant shows only limited transcriptional activity in tissue culture based assays and functions as a dominant-negative at both the phenotypic and molecular levels in vivo. These features represent aspects of both dominant gain-of-function and dominant-negative activities and imply that the functions of DNA binding can be functionally separated from the role of STAT92E as a transcriptional activator. It is thus possible that an alternative post-translational modification, in addition to tyrosine phosphorylation, may be required to allow STAT to act as a transcriptional activator and suggests the existence of an alternative mechanism by which STAT transcriptional activity may be regulated in vivo.